1990
DOI: 10.1128/aac.34.12.2442
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibility of Mycobacterium avium complex to the new fluoroquinolone sparfloxacin (CI-978; AT-4140) and comparison with ciprofloxacin

Abstract: We tested the activity of the new fluoroquinolone sparfloxacin ; AT 4140) against 30 strains of Mycobacterium avium complex (MAC) isolated from patients with acquired immune deficiency syndrome.MICs of sparfloxacin (range, <0.06 to 4 pg/ml) were lower than MICs of ciprofloxacin for all 30 strains, andMBCs for acid-fast bacteria were lower for 28 of the 30 strains. In synergism experiments using 10 strains of MAC, fractional inhibitory concentration indices revealed that the combination of sparfloxacin plus eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 12 publications
(23 reference statements)
0
16
1
Order By: Relevance
“…Hydrophobic solutes can penetrate the barrier [1]. Antibiotics of the most hydrophobic types for example, are also the most effective drugs against mycobacteria [3,4].…”
Section: The Envelope Of Mycobacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrophobic solutes can penetrate the barrier [1]. Antibiotics of the most hydrophobic types for example, are also the most effective drugs against mycobacteria [3,4].…”
Section: The Envelope Of Mycobacteriamentioning
confidence: 99%
“…Hydrophobic solutes can penetrate the barrier [1]. Antibiotics of the most hydrophobic types for example, are also the most effective drugs against mycobacteria [3,4].Considering the extreme rigidity and impermeability of the outer permeability barrier [5] of M. tuberculosis, it is a paradox that liquid cultures contain excessive amounts of soluble proteins which are much larger than the small solutes referred to above and do not have the hydrophobic properties that would make them pass. To explain the presence of the large quantities and wide repertoire of proteins in the culture filtrates, it is necessary to suggest that there is a mechanism for protein transport across the outer permeability barrier, maybe some kind Scand.…”
mentioning
confidence: 99%
“…The permeation ability of a lipophilic molecule is inversely related to the fluidity of the cell wall, which decreases as the length of fatty acids in the MA layer increases (51). Lipophilic drugs, such as fluoroquinolones or rifamycins, pass more easily through the lipid-rich cell wall and thus are more active (51,451).…”
Section: Why Are Mycobacteria So Innately Resistant To Antibiotics?mentioning
confidence: 99%
“…Its structure is similar to that of ciprofloxacin; however, it has two methyl groups in the piperazinyl ring and an additional fluorine atom at position 8, which, according to Schentag and Domagala (17), enhances its activity against grampositive organisms. Nakamura (13) and others (4,18,19) reported that sparfloxacin has a broad antibacterial spectrum that includes the pathogens mentioned above, which are not sufficiently susceptible to other quinolones. The present in vitro study was designed to establish (i) the antibacterial activity of sparfloxacin compared with those of other quinolones, (ii) the influence of changes in the pH of the culture medium, inoculum size, and Mg2+ concentration on the activity, (iii) the postaiitibiotic effect (PAE), and (iv) the in vitro mutational frequency rate to sparfloxacin resistance in a number of key pathogens.…”
mentioning
confidence: 99%